Note of conversation with William Gillies - Gillies, William; F.P.
011-0148-001 5.2.37. Mr Gillies said A Mr Heisswein + a Mr Ecklen (M.P for Antwerp + a T.U. leader) are seeing him at 11.15 today. Probably about Spain. Would Sir Walter give him some advice as to the line he (Sir Walter) would take. F.P. Will he hear what they have to say without making commitments. 292/946/11/148